Temps numériques et contretemps pédagogiques en Collège Connecté - Pascal Plantard (Centre National d'Enseignement à Distance, 2016)
From September, 2013 till June, 2015, our team of eight researchers and four students immersed themselves for 2 school years in the everyday life of a connected Middle School (COCON) in Brittany (France). This article will focus on the modelling of the routes of appropriation of the digital technologies by the teachers articulating their implicit educational models (axis, praxis, psyche) with the anthropological processes of construction of the uses of digital technologies, internal (Poaching, Odd Jobbing and Gathering) and external (techno - imagination, representations, practices, uses). The questions of temporality will be mobilized to understand how the subjective and concrete aspects of the COCOON project influenced the teachers' working time and which consequences these temporal transformations had on the implementation of the project and on the teachers' investment. We shall present the results of this search around ideal-typical portraits illustrating the notion of "route" anchored temporarily in four different phases (bait, confidence, construction, empowerment).